Pengaruh Kinerja Keuangan Perusahaan Terhadap Opini Audit Going Concern - de Haan, Joshua Adry Philander; Sari, Martdian Ratna (Journal of Emerging Business Management and Entrepreneurship Studies, 2023)
This research aims to assess the influence of financial performance on going concern audit opinions during the Covid-19 pandemic. The going concern issue has become increasingly relevant due to the pandemic's impacts. The study involves 429 sample data from manufacturing companies listed on the Indonesia Stock Exchange (BEI) from 2019 to 2021. The research method applied is associative research, which aims to explore the correlation between profitability, liquidity, solvency, and activity ratios with audit opinions related to the continuity of operations (going concern). The data analyzed in this study are quantitative data obtained from companies' financial reports and accessed through the official website of the Indonesia Stock Exchange (BEI). The statistical method used to analyze this data is logistic regression analysis. The research results reveal that when analyzing variables separately, the debt-to-assets ratio and total assets turnover have an impact on going concern audit opinions, while return on assets, return on equity, gross profit margin, net profit margin, current ratio, quick ratio, cash ratio, debt to equity ratio, fixed asset turnover, and inventory turnover do not have an impact on going concern audit opinions.